A THIRD WAY OF SPIRITUALITY BEYOND FAITH AND REASON IN BUDDHISM - Sharma, Arvind (Journal of Dharma, 1988)
A popular book on the philosophy of religion contains the following epistemological observation: "Philosophy recognizes two ways in which human beings may come to know whatever there is to be known. One way (stressed by empiricism) is through experience, and the other (stressed by rationalism) is through reasoning.’" Three points need to be made before proceeding any further. The first is that the word experience here must be taken as confined to normal sensory experience and excludes both extra-sensory perception and mystical experience. The second is that experience and reason can be combined as a way of knowing which one might call rationalism, as reason operates within the realm of sensory experience. The third point is that although philosophy of religion discusses the nature of faith3 it does not, unlike theology, accept it as a way of knowing.